Low-cost solar based battery charger - Lim, Jun Wei (Nanyang Technological University, 2021)
Due to global warming, there is an increasing need to generate electricity with renewable sources. Singapore’s location near the equator is a prime spot to utilize PV technologies. However due to limited land space, PV installations were limited in HDB residential areas and mainly carried out in industrial areas and landed properties. Thus, there is limited opportunities for HDB residents to take advantage of PV technology products to play a part in reducing their carbon footprint. The objective of this project is to design a low-cost solar battery charger on PSIM Maximum power point tracking is achieved by utilizing the zeta converter and incremental conductance MPPT method. When the battery is in full-charge status, power generated by the PV array will be fed into the grid.